The Role of Education in Developing Spirit - Korompis Rangga Aldo; Kasingku Juwinner Dedy (Edumaspul: Jurnal Pendidikan, 2023)
Holistic education plays an important role in shaping the enthusiasm for learning in every individual. It emphasizes the connection between physical, emotional, social, and moral aspects of the developmental process, going beyond mere academic achievements. This article uses a qualitative literature review approach to discover the link between holistic education and enthusiasm for learning. Teaching aligned with God’s word has a vital role in shaping character, knowledge, and a stable moral foundation. This article also outlines how holistic education and teachings based on God’s word are interconnected, assisting individuals in guiding their lives according to the principles contained in the scriptures. This approach also aids individuals in understanding their beliefs and can trigger sustained enthusiasm for learning. Through a holistic approach aligned with teachings from scripture, individuals are expected to become enthusiastic learners, possess good morals, and contribute positively to society and their overall lives. Therefore, holistic education based on the values of God’s word can provide a strong foundation for learning.